ANALISIS PENGARUH ARUS KAS BEBAS, STRUKTUR MODAL, DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN PROPERTY, REAL ESTATE DAN BUILDING CONSTRUCTION - Taniel, Levi; Tjakrawala, Kurniawan (Jurnal Paradigma Akuntansi, 2025)
The aim of this research is to see the effect of free cash flow, capital structure, and this investment opportunity set on dividend policy based on financial reports that have been written by property companies listed on the Indonesia Stock Exchange (IDX). In this study, the population was obtained using a purposive sampling technique for property, real estate and building construction companies listed on the IDX with criteria including property, real estate and building construction companies that have financial report data for the 2018-2021 period . Based on the sampling method, there were 17 property companies. The analysis of this research is multiple linear regression analysis assisted by SPSS Version 21 software and Microsoft Excel 2016. This research has proven that the investment opportunity set has a positive effect on dividend policy. This study cannot prove that free cash flow has a positive effect on dividend policy and that capital structure has a negative effect on dividend policy.